Efek Inokulasi Bakteri Pemfiksasi N dalam Carrier Organik terhadap Pertumbuhan dan Hasil Padi Gogo pada Inceptisol - Suryatmana, Pujawati; Setiawati, Mieke Rochimi (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2025)
National rice production in Indonesia is supported by two main rice-growing types—lowland (paddy) and upland (dryland) rice. Lowland rice contributes a larger share to national rice productionthan upland rice. However, several constraints in lowland rice cultivation may hinder efforts to furtherincrease its productivity. One alternative approach to address these constraints is the development ofupland rice cultivation. The objective of this study was to investigate the effects of urea fertilizerdosage and nitrogen-fixing bacteria (NFB) applied with different carrier materials (compost, amixture of compost and rice bran, and Azolla) on the growth and yield of upland rice grown onInceptisols in Jatinangor. The experiment was arranged in a randomized block design with twofactors: urea fertilizer dosage (100% and 50% of the recommended rate) and the application ofnitrogen-fixing bacteria using various carrier materials (compost, rice bran, and Azolla meal) as wellas a liquid culture without a carrier. The results demonstrated that the effect of urea dosage wasindependent of the nitrogen-fixing bacteria applied using carrier materials. Individually, thetreatments were not significantly affected the population of Azotobacter spp. and Azospirillum spp.,plant height, number of panicles, or 1,000-grain weight of upland rice. However, the nitrogen-fixingbacteria inoculation with a mixed carrier (compost, rice bran, and Azolla) significantly increased filledgrain weight, resulting in the highest average filled grain yield of 37.30 g per plant.